Current Practice for the Management of Blunt Abdominal Trauma in a Tertiary Care Hospital: A Prospective Study - Shah Nawaz Khatti, Abdul Latif, Sorath Bukhari, Ajmal Khan Bazai, Sidra Fatima Afzal, Kanwal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the different kinds of management provided to patients with Blunt Abdominal Trauma (BAT) in the surgical department of a tertiary care hospital. Study design: prospective study Place and Duration: This study was conducted at Liaquat University of Medical and Health Sciences Jamshoro from March 2021 to March 2022 Methodology: The present study includes 115 patients who presented with blunt abdomen trauma (BAT). The data was collected with the pre-designed questionnaire. Data were collected prospectively from all patients admitted to the hospital with abdominal trauma. The trauma was treated using ATLS (Advanced Trauma Life Support) techniques. Laboratory and imaging investigations were performed to diagnose and manage the patients. SPSS version 21 was used to analyze the data. Descriptive statistics were presented in mean, SD/median, frequency, and percentage. Results: During the investigation, 115 BAT patients were examined. The average age of the patients was 33.7 ± 7.2 years. Males (n=94, 81.7%) and symptomatic cases (n=108, 94%) made up the majority of the injured patients. More than half of the patients (n=73, 63.5%) had abdominal tenderness when they arrived. The majority of the patients had X-rays (n=87, 75.6%) ultrasound (n=75, 65.2%), lab investigation (n=83, 72.1%) and abdominal CT scan (n=35, 30.4%). Only a few patients died (n=17, 14.8%). Patients were treated conservatively in 83% of cases, while surgical treatments were used in 17% of cases. Conclusion: Non-operative therapy has become the gold standard for critically stable patients with traumatic injuries. Although non-operative management has a higher risk of failure in patients with multiple solid organ injuries, it should still be used with caution in most critically stable persons who do not have peritoneal symptoms. Keywords: Accident, Blunt Abdominal Trauma (BAT), Non-operative management, vitally stable.